WASTEWATER QUALITY PARAMETERS AND METHANE PRODUCTION IN DANDORA ESTATE SEWERAGE TREATMENT WORKS, NAIROBI CITY COUNTY, KENYA - Mabonga, Michael Kiboi; Maingi, Dr. Simon M.; Kirubi, Dr. Gathu (International Journal of Environmental Sciences, 2020)
Purpose: The purpose of this study was to establish wastewater quality parameters and methane production in Dandora Estate Sewerage Treatment Works, Nairobi City County, Kenya Methods: Dandora Estate Sewerage Treatment Works has 38 ponds in eight series. There are two anaerobic ponds, six primary facultative ponds, eight secondary facultative ponds and twenty-two maturation ponds. Methane production can occur in a pond exceeding a depth of two meters, therefore anaerobic ponds (4.7 meters) and facultative ponds (2.7 meters) were considered. Laboratory research was performed to measure the amount of biological oxygen demand, chemical oxygen demand, total solids, temperature, pH, dissolved oxygen, and wastewater inflow and outflow volumes. Results: The findings of the study revealed that Methane production is dependent on typical wastewater parameters such as pH, BOD, COD, TOW and temperature. Total organics in the wastewater is directly proportional to methane production and has a t-value of 6.425. pH and methane production have a negative correlation of -0.297 in the domestic wastewater and -0.335 from industrial sources. Increase in pH above neutral pH value 7 leads to increased alkalinity leading to reduced enzyme activity thus reduction of methane production. BOD and COD in the wastewater is affected by total organics in the wastewater. BOD is directly proportional to methane production and has a correlation value 1.0 with a t-value -5.431. COD and methane production have a correlation of 0.75. Methane production is affected my both BOD and COD in the wastewater. Unique Contribution to Theory, Practice and Policy: The study recommended that it was important to separate domestic wastewater from industrial wastewater to allow for future efficient methane gas inventories to be conducted.